Mobile Tourism Application BasedOn Situation Awareness (International Journal of Engineering and Computer Science, 2014)
The process of searching, selecting, grouping and sequencing destination related products and services including attractions, accommodations, restaurants, and activities included in the travel and tour planning. In tour planning, there are many mobile tourism applications developed. These tourism, mobile applications is changing the way of travelers plan and experience tourism in the future. The previous research investigated the development of context awareness, mobile applications for the tourism industry. Various aspects of context awareness are applied in tour guide companions and recommendation systems. However, these contexts awareness, mobile applications do  not  improve  travelers’  situation awareness, especially in pre-visiting and during visiting phases. In other words, when using mobile applications, travelers may not perceivethe situation correctly, fail to comprehend the situation or they are unable to anticipate the future development. We propose mobile tourism application using situation awareness. The semantic web technology and MES technique for showing Situation Awareness is discussed here. The proposed design shows scenarios of traveler visiting experiences are shown and suitable designs for each scenario are discussed. The proposed design will implement the mobile tourism application for Mumbai region.